EU Postal Directives and Croatian Regulatory Frame - Tabak, Pero; Kaštela, Slobodan (Promet - Traffic&Transportation, 2012)
The paper compares the EU Postal Directives (97/67/EZ and 2002/39/EZ) in a consolidated text and the respective parts of the Croatian legislative frame with the aim of harmonising the national postal system with EU. Both regulatory frames are presented, as well as objectives and scopes, types of postal services (particularly the universal ones), reserved area, necessary conditions governing the provision of services, tariff principles, insurance of market competition through transparency of financing and separation of the accounting system, desired quality of universal services, harmonisation of technical standards and obligations of national regulatory authorities. By presenting individual chapters of the Post Directives, some specific solutions of the Croatian regulatory framework have been indicated and uncertainties which result from the comparison analysis of the European Postal Directives and the Croatian legislation as well as the influence of these documents on the postal traffic technology. KEY WORDS: EU Postal Directives, Croatian postal regulatory frame, universal services